Automatic attention to sexual stimuli: exploring the role of neuroticism and sexual excitation/inhibition through event-related potentials. (24th January 2023) - Aguiar, Sandra; Carvalho, Joana; Carrito, Mariana L; Santos, Isabel M
Abstract: Background: Previous findings have shown that neuroticism is a higher-order vulnerability factor in the development and maintenance of sexual dysfunctions and can have an impact on the attentional processing of sexual stimuli; however, the influence of psychosexual dimensions on the early automatic phases of such cognitive processes has not been established yet. Aim: To examine the mediating role of sexual inhibition/excitation propensity in the relationship between neuroticism and automatic attention to visual erotica and to identify the neuroelectric correlates of such a process. Methods: We analyzed the answers provided by 58 individuals on the Neuroticism subscale of the NEO Personality Inventory–Revised and the Sexual Inhibition/Excitation Scales. Event-related potentials (ERPs) were recorded during a modified oddball paradigm containing romantic and sexually explicit pictures. Parallel mediations were performed to simultaneously test the mediating role of sexual inhibition/excitation in the relationship between neuroticism and each ERP. Outcomes: Three early attention ERP components (P1, P2, and N2) were assessed. Results: Findings revealed an indirect effect of neuroticism on automatic attention, via sexual inhibition due to threat of performance failure (SIS1), for romantic and sexually explicit stimuli. This effect was significant only for component N2, which showed increased amplitudes and earlier latencies in participants with high SIS1. Clinical Implications: Sexual stimuli, due to their emotional valence and arousal potential, might be perceived as virtually threatening by individuals with neuroticism, who may benefit from strategies that decrease hyperarousal and sympathetic activation. Strengths and Limitations: This was one of the first studies to analyze neuroelectric activity associated with automatic attention toward sexual stimuli in relation to personality and sexual excitation/inhibition propensity. Nevertheless, the limited number of participants demands caution in generalizing the results. Conclusion: These results provide a better understanding of the relationship between personality and sexual cognition and open new avenues of research in relation to other automatic cognitive phenomena related to human sexual behavior.